Culminating Final Year Project Experiences Among Computing Undergraduate Students in UPSI - Muhammad Modi Lakulu; Maizatul Hayati Mohamad Yatim; Laili Farhana Md Ibharim (Pejabat Karang Mengarang UPSI, 2021)
Articles placed in the session of Vol 8 No 3 (2021): Special Issue 1/2021: Culminating Experiences dedicated to the Journal of Information and Communication Technology in Education (JICTIE) were composed from ten (10) final year projects from undergraduate students of Computing Department in the Faculty of Arts, Computing and Creative Industries, Universiti Pendidikan Sultan Idris (UPSI), Tanjong Malim, Malaysia. Six articles were produced by students from Bachelor of Education (Information Technology), one article from Bachelor of Education (Multimedia), and three articles from Bachelor of Software Engineering (Educational Software) programs. All articles were written by the students as first authors in collaboration with their supervisors and respective co-authors.